Bilan 2004 du réseau REPAMO - Réseau national de surveillance zoosanitaire des mollusques marins - Garcia, Celine; Arzul, Isabelle; Chollet, Bruno; Francois, Cyrille; Goubet, Anne; Joly, Jean-pierre; Miossec, Laurence; Robert, Maeva; Cuvelier, Nicolas; Lefebvre, Alain; Le Gagneur, Eric; Ropert, Michel; et al. (2005)
Created in 1986, the REPAMO network (Network of mollusc pathology), is a national zoosanitary surveillance network of shellfish health status along the French coasts. Its activities are in keeping with two European Directives, 91 /67/EEC and 95/70/EC and are a patt of the institutional tasks ofIfremer. The aims of the network are to prevent the introduction and spread of exotic pathogens and to survey the evolution of notifiable pathogens already present in France. The network focused on the survey of listed diseases (bonamiosis and marteiliosis of flat oyster) in two areas under agreement process (Banc de Granville and zone X). In 2004, no sample couId be analysed to these two areas because of the difficulty to obtain flat oysters (sparse oyster beds, beds no easy accessible).In 2004, the study of abnormal mortalities has been carried on and the number of reported cases is lower than 2003 which was a special year (summer heatwave in august). Mortality occured mostly in summer and the main impacted areas were South Brittany, Arcachon Bay and Normandy. Majority reports concerned Pacific oyster, Crassostrea gigas. Nevertheless, several abalone mortalities were recorded in abalone farms and in one abalone bed. Sorne pathogens were detected associated with mortality cases but ail the mortality cases could not be explained by the pathogens. Environmental, physiological, zootechnical factors couId play a direct or indirect part in reported mortalities. Since 2003, the pathogen detection during abnormal mortalities seems more frequent than the previous years; this increase can be explained by the network restructuring and the better reactivity of shellfish farmers. The new sampling strategy of zoosanitary surveillance of cultured and wild populations of shellfish was carried out and concerns for the years 2004-2005 the clams Ruditapes decussatus and R. philippinarum particularly their infection by the parasite Perkinsus olseni. This preliminary study showned that Perkinsus olseni is present in the main production areas ...